2011
DOI: 10.1128/jvi.05126-11
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Human Papillomavirus E6 and E7 Oncogenes through Expression of the Bovine Papillomavirus Type 1 E2 Protein Stimulates Cellular Motility

Abstract: Expression of the high-risk human papillomavirus (HPV) E6 and E7 oncogenes is essential for the initiationHigh-risk human papillomavirus (hrHPV)-positive cervical cancer cells harbor integrated HPV genomic DNA and are uniquely dependent upon the expression of two viral oncogenes, E6 and E7, for the maintenance of the transformed phenotype (40). hrHPV E6 is best known for its ability to target p53 for proteasomal degradation via its association with the E6-associated protein (E6-AP), a ubiquitin ligase (52,53,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…It is of note that the alteration in the expression and splicing of genes involved in cell movement and motility were detected and that the E2 expressing cells had a reduced cellular motility when compared with wild type cells. A recent paper demonstrated that E2 can up regulate cell motility but this was done in the background of HPV positive cells making it difficult to compare with the results presented here (Morrison et al, 2011). In cervical cancers the HPV genome is integrated in the majority of cases, resulting in loss of the E2 gene (Mair et al, 2014; zur Hausen, 2009).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It is of note that the alteration in the expression and splicing of genes involved in cell movement and motility were detected and that the E2 expressing cells had a reduced cellular motility when compared with wild type cells. A recent paper demonstrated that E2 can up regulate cell motility but this was done in the background of HPV positive cells making it difficult to compare with the results presented here (Morrison et al, 2011). In cervical cancers the HPV genome is integrated in the majority of cases, resulting in loss of the E2 gene (Mair et al, 2014; zur Hausen, 2009).…”
Section: Discussionmentioning
confidence: 63%
“…There have been few studies investigating the direct role of E2 in regulating host gene expression outside of the HPV cell line systems where over expression results in repression of E6 and E7 expression and reactivation of the p53 and pRb tumor suppressor pathways (Desaintes et al, 1997; Goodwin et al, 1998; Hwang et al, 1996; Johung et al, 2007; Morrison et al, 2011; Naeger et al, 1999; Parish et al, 2006; Thierry et al, 2004; Wu et al, 2000). Such reactivation results in cell cycle arrest and apoptosis and expression of E2 in these cells results in activation of genes and pathways involved in these processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of E6 and E7 expression by estrogen could result in the elevation of p53 and pRb expression (their respective tumor suppressor targets)(2841). Previously, studies have shown that when E2 is overexpressed in HPV positive cervical cancer cells it represses transcription from the viral LCR and this repression reduces E6 and E7 levels and reactivates the p53 and pRb tumor suppressor proteins(31, 4244, 4450). Moreover, E2 overexpression and loss of E6/E7, results in the elevation of p53 and pRb that allows for previously observed attenuation of growth in HeLa cells(23, 31, 45, 46, 48).…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic keratinocyte HPV-16 E6/E7 promotes cell immortalization [70] Ectocervix keratinocyte HPV-16 E6/E7 promote cell immortalization [71] Normal foreskin keratinocyte E6 increases telomerase activity [72,73] COS7 cells HPV-1 and 8 E6 interacts with E6AP (ubiquitin) and p53 [74] Normal foreskin keratinocyte HPV-16 E6 promotes epithelium stratification reduction [75] Immortalized keratinocyte Evidences of HPV-16 productive infection [76] Murine C127 cells HPV-16 and BPV-1 E6 promotes focal adhesion decrease [77][78][79] Wart and squamous carcinoma HPV E6 inhibits apoptosis in response to UV damage [80] Normal foreskin keratinocyte HPV-16 E6/E7 induce cytogenetic aberration [81,82] Chondrocyte HPV-16 E6/E7 promotes immortalization and collagen type II expression [83] Normal foreskin keratinocyte HPV-16 E6 induces p53 degradation and p53 and hTERT expression, increasing telomerase activity [84] Normal foreskin keratinocyte HPV-16 E6/E7 induce irreversible epitelialmesenchymal transition [85] Cervical keratinocyte HPV-16 E5 interacts with endoplasmic reticulum membrane [86] Normal foreskin keratinocyte HPV-16 E6/E7 promote epigenetic alterations in host cell [87] Normal foreskin keratinocyte HPV-16 E1^E4 induce keratin reorganization [88] Normal foreskin keratinocyte BPV-1 E2 stimulates cell migration [89] Keratinocyte (PM1) HPV-8 E2, E6 e E7 promote the stem-cell phenotype acquisition [90] HEK293 cells Domain PDZ da E6 induces PKAand AKT phosphorylation [91] U2OS cells E2 binds to Brd4 regulating DNA replication [92] freezing medium (70% DMEM, 10% dymethylsulphoxyde and 20% FBS) and stocked at -196ºC. These cell lines are part of biological collection of Genetics Laboratory.…”
Section: Cell Typementioning
confidence: 99%